2012
DOI: 10.1021/ma301170x
|View full text |Cite
|
Sign up to set email alerts
|

Phototriggered Mass Migration Consorted with Surface Dewetting in Thin Films of a Liquid Crystalline Azobenzene-containing Dendrimer

Abstract: A dendritic molecule of poly(propylene imine) whose periphery is modified with photoresponsive mesogenic azobenzene units was synthesized. This compound exhibited highly ordered smectic B or smectic A layer structure orienting parallel to the substrate in the film state. When this film of 90 nm thickness on a hydrophilic substrate was exposed to UV (365 nm) light, the initial flat film morphology started to form holes followed by a drastic transformation to form separated dome structure of micrometer levels. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…We used a commercially available 5CB liquid crystal (Sigma-Aldrich) mixed with 0.1 wt% of poly(propyleneimine)-based azo-dendrimers (32). Glass microrods of a diameter 1.49 ± 0.07 μm and lengths between 10 μm and 25 μm (PF-15S, Nippon Electric Glass) were mixed with the LC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a commercially available 5CB liquid crystal (Sigma-Aldrich) mixed with 0.1 wt% of poly(propyleneimine)-based azo-dendrimers (32). Glass microrods of a diameter 1.49 ± 0.07 μm and lengths between 10 μm and 25 μm (PF-15S, Nippon Electric Glass) were mixed with the LC.…”
Section: Methodsmentioning
confidence: 99%
“…Li et al recently synthesized a photosensitive dendrimer with azo linkages (azo-dendrimer) in the mesogenic end chains (Fig. S1) and demonstrated the adsorption of the dendrimer at a glass interface (32). By UV irradiation, an orientational change of the mesogenic moieties occurs associated with the trans−cis photoisomerization, as illustrated in Fig.…”
mentioning
confidence: 99%
“…Yonetake et al synthesized and evaluated the LC properties of poly(propylene imine) dendrimers peripherally modified with cyanobiphenyl mesogens. Utilizing this framework, Li et al showed that particular photoinduced surface dewetting takes place in a film of a relevant dendritic azobenzene derivative on a hydrophilic surface upon UV light irradiation (Table , 41 ). Interestingly, when the film was subjected to mass migration with patterned UV light, consorted motions of mass transfer and surface dewetting provided hierarchical relief structures.…”
Section: Mass Migrations In Lc Film Systemsmentioning
confidence: 99%
“…Photochromic reactions have frequently been incorporated in LC media because of their repeatability for controlling material properties. This approach has provided various types of smart, light-responsive materials 1 exhibiting surface-mediated photoalignment of LC materials, [2][3][4][5][6] photoinduced phase transitions, [7][8][9][10][11][12] photoorientation/addressing of polymer thin films, [13][14][15][16][17][18] photoinduced mass migrations, [19][20][21][22][23][24][25][26][27][28] phototactic sliding motions, [29][30][31] photo-driven motions and morphology of monolayers, [32][33][34][35] and macroscopic photomechanical deformations. [36][37][38][39][40][41][42][43][44][45][46] Photoalignment research and technology started in 1988 with the discovery of the reversible alignment control of nematic LCs by the photoisomerization of azobenzene on a substra...…”
Section: Introductionmentioning
confidence: 99%